PENGARUH LITERASI KEUANGAN DAN PENDAPATAN TERHADAP PERENCANAAN KEUANGAN DANA PENDIDIKAN ANAK (STUDI KASUS Pada IBU RUMAH TANGGA) - Bunga Vidyaningrum; Ch Dini Ika Handayani (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
The purpose of this study is to analyze financial literacy and financial planning on educational funds for children among housewives. Financial literacy and income become a motivating factor for an individual to make an investment decision. The desire to get more income and invest to get profits in the future. The participants of this study are 100 housewives in Yogyakarta. Data collection technique is using distribution questionnaires and conducting interviews to obtain more in-depth information. The collected data was analyzed using statistic descriptive analysis approach to investigate the level of financial literacy and financial planning on the children educational funds. The results of research conducted partially indicate that there is a significant influence of financial literacy and income on financial planning for educational fund. And simultaneously indicate that there is an influence of financial literacy and income on financial planning for educational fund.